Understanding adolescent depression in Singapore: a qualitative study - Ngar Yee Poon; Cheryl Bee-Lock Loh (Singapore Medical Journal)
Introduction: This qualitative study aimed to understand the lived experiences of adolescents with depression seeking help in our healthcare system, with the focus on initial symptoms, experience of care and reflection after recovery. Methods: Semi-structured interviews were conducted with 14 adolescents, aged between 13 and 19 years, who were diagnosed and treated for diagnostic and statistical manual of mental disorders, 5th edition major depressive disorder and clinically judged to have recovered at the time of recruitment. Data were analysed qualitatively using thematic analysis, with a focus on how the adolescents spoke about their experience of depression. Results: The findings suggested that our adolescent participants had initially tried managing depression within their own circle, and that thoughts of suicide and self-harm, as well as anhedonia–avolition symptoms were the most challenging to deal with. Recovered participants were observed to express a high degree of empathy towards others going through depression. Conclusion: This study is the first to have surveyed adolescents in our Asian city-state on multiple aspects of their experience of depression. It allows a wide-ranging description of this condition and has the potential to improve understanding and inform care delivery.